The Effect of Project Based Learning Combined with Digital English Book on Students’ Speaking Skill - Veronica Desiana Puspitasari; Nina Sofiana (Journal on Education, 2024)
This study aims to find out the effectiveness of Project Based Learning as a tool combined with Digital English Book. This research focused exploration of the problem of students speaking skill, strives to know about the method and the media that can use to see what extent it assist on students' speaking skill. This research will be conducted at MA Miftahul Huda Bulungan Jepara involving two classes from grade ten. Through saturated sampling, 80 students are selected to be involved in being a research sample by contributing to a project to see the development of students' speaking skills. In this research, pre-test and post-test research methods were used to compare students' speaking skills before and after being given treatment. The result is using Project Based Learning combined with Digital English Book is proven to be effective in learning because there is a significant increase in students' speaking skills. The analysis result by using the independent sample T-test is indicate that the T-test was higher compared to T-Table score (3,013>1665). It means that the alternative hypothesis is accepted and the null hypothesis is rejected. In conclusion, the effect of Project Based Learning that combined with Digital English Book is effective to improve students’ speaking skill.